The new development direction of seismic gravity observation technology: Integrated measuring of absolute gravity and vertical gravity gradient - Qiong Wu; Jiansheng Xu (地震科学进展, 2023)
The integrated and array observation of the high-precision absolute gravity and gravity gradient can effectively improve the identification accuracy of gravity field sources at different depths. Based on the shortcomings and development direction of absolute gravity observation technology in the “China Geophysical Station Network (Gravity) Planning (2020—2030)” issued by the China Earthquake Administration, this paper proposes the observation technology idea of the integration of absolute gravity and gravity gradient. By monitoring and discovering the microgravity change signals caused by the transport of shell-mantle hot materials during the incubation of strong earthquakes, the ability to predict medium-term, short-term and near-earthquakes of destructive earthquakes is improved. The application of absolute gravity control capabilities of gravity station networks is further expanded to explore new development directions of gravity observation technology for professional seismic stations in China.